Bimetal catalyst based on Fe and Co supported on Al pillared interlayer clays: Preparation, reactivity and mechanism for SCR-CH4 - Shuying Ning; Shasha Huang; Honghai Yang; Bingtao Zhao; Yaxin Su (iScience, 2023)
Summary: Montmorillonite was used as raw clay to prepare the Al-pillared interlayer clay (Al-PILC) as support by impregnation methods. Co and Fe were loaded in series on Al-PILC to prepare the bimetal catalysts (Fe-Co/Al-PILC). The SCR-CH4 was evaluated in a fixed bed reactor and the results indicated that 0.27Fe-Co/Al-PILC exhibited 100% N2 selectivity and above 63% NO conversion in the presence of 10% H2O, and the introduction of Fe significantly improved the Co/Al-PILC catalyst’s resistance to H2O and SO2. Characterization showed that Lewis and Brønsted acids co-existed on the catalyst surface, and the Lewis acid was the dominant active acid site and enhanced the activation of methane over the 0.27Fe-Co/Al-PILC. Fe promoted the formation of isolated Co2+ and CoO species, and the isolated Fe3+ particles improved CH4-SCR performance. The reaction route was proposed based on in situ DRIFTS tests and the active intermediates were mainly various nitrates and nitromethane (CH3NO2).